Immature Citrus unshiu fruit extracts inhibit adipogenesis in 3T3-L1 adipocytes via AMPK and MAPK signaling pathways - Min Gun Kim; Kyung-Hwan Boo; Jae-Hoon Kim; Chang Sook Kim (PLoS ONE, 2025)
In Korea, immature citrus fruits have been extensively explored for their potential utility as functional bio-health materials owing to their various bioactive properties. However, the specific mechanisms by which they exert inhibitory effects on adipogenesis remain unclear. Therefore, this study aimed to examine the anti-obesity effects of 70% ethanol extracts of immature Citrus unshiu fruits and their solvent fractions (n-hexane, ethyl acetate, n-butanol, and water) on 3T3-L1 cells, as well as to explore the underlying molecular mechanisms. Additionally, this study was conducted to identify the bioactive components responsible for the anti-obesity effects. Among the fractions, the hexane fraction exhibited the most potent inhibitory effect on lipid accumulation in 3T3-L1 cells without inducing cytotoxicity. Notably, this effect was concentration-dependent. This fraction also inhibited adipogenesis during the differentiation of 3T3-L1 preadipocytes by downregulating the expression of CCAAT/enhancer-binding proteins (C/EBP), peroxisome proliferator-activated receptor-γ (PPARγ), sterol regulatory element-binding protein (SREBP), fatty acid synthase (FAS), and fatty acid binding protein 4 (FABP4). Moreover, the hexane fraction modulated the activity of AMP-activated protein kinase (AMPK) and mitogen-activated protein kinase (MAPK), both of which play critical roles in lipid metabolism. Specifically, it induced AMPK activation while downregulating MAPK signaling. Phytochemical analysis identified phytol, hexatriacontane, tangeretin, and nobiletin as the main bioactive components responsible for the observed anti-obesity effects of ICE. Overall, our results revealed that ICE exhibited notable anti-obesity activity by targeting the AMPK and MAPK signaling pathways, highlighting its potential as a natural therapeutic agent for obesity management.